Pembelajaran Qi’raah dengan Strategi Tartib al-Nash di Madrasah Aliyah - Tutin R Ali; Muhammad Nur Iman; Suharia Sarif; Geini Alfirani Mokoagow (Faculty of Education and Teacher Training, 2024)
This study investigates the application of the Tartib al-Nash method to enhance Arabic reading skills among tenth-grade students at Madrasah Aliyah al-Mujahidin Molas. The background highlights the importance of Arabic language proficiency in understanding Islamic literature, which is integral to the curriculum at Madrasah Aliyah. Despite this, students often struggle with reading complex Arabic texts due to limited vocabulary and ineffective reading strategies. The study's objective is to address these challenges by implementing Tartib al-Nash, a method that organizes text systematically to aid comprehension. The research employs a Classroom Action Research methodology, following the Kemmis and McTaggart model, which involves planning, action, observation, and reflection cycles. The study is conducted over two cycles, each consisting of three sessions, with the participation of nine students. Data collection methods include tests and observation sheets, and data is analyzed qualitatively. Results indicate a significant improvement in students' reading skills, with a marked increase in their ability to organize and comprehend Arabic texts. The conclusion suggests that Tartib al-Nash is an effective strategy for enhancing Arabic reading skills, with potential implications for broader educational practices in similar contexts.